2017
DOI: 10.1002/tea.21408
|View full text |Cite
|
Sign up to set email alerts
|

Examining the reasoning of conflicting science information from the information processing perspective-an eye movement analysis

Abstract: The main goal of this study was to investigate how readers’ visual attention distribution during reading of conflicting science information is related to their scientific reasoning behavior. A total of 25 university students voluntarily participated in the study. They were given conflicting science information about earthquake predictions to read while their eye movements during reading were recorded by the FaceLAB eye tracking system. After reading, the participants were interviewed to probe their reasoning p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…As this task's solution did not demand extra processing, this result points to their effort to solve the task. 46,47 AOIs, the students fixated on the legend significantly (p = 0.001) shorter than the relevant and irrelevant AoIs. The value η 2 = 0.621 represents a large effect size.…”
Section: Students' Use Of Periodic Tablementioning
confidence: 94%
“…As this task's solution did not demand extra processing, this result points to their effort to solve the task. 46,47 AOIs, the students fixated on the legend significantly (p = 0.001) shorter than the relevant and irrelevant AoIs. The value η 2 = 0.621 represents a large effect size.…”
Section: Students' Use Of Periodic Tablementioning
confidence: 94%
“…In addition, prior knowledge and spatial ability may influence science reading and science learning (Hodgkiss et al, 2018;Kozhevnikov & Thornton, 2006;van den Broek, 2010;Vosniadou & Skopeliti, 2018;Yang, 2017). As for prior knowledge, Patterson et al (2018) indicated that reading comprehension of science texts influences learning of scientific concepts.…”
Section: Relevant Factors That Influence Reading Comprehension and Hands-on Manipulationmentioning
confidence: 99%
“…In science reading comprehension, students need to organize various pieces of scientific information to form a new concept, and their prior knowledge can influence how they read texts and link it to science propositions (van den Broek, 2010). Vosniadou and Skopeliti (2018) indicate that poor prior knowledge leads to the forming of misconceptions, and Yang (2017) found that it is associated with weaker scientific reasoning. As for spatial ability, Kozhevnikov and Thornton (2006) show that spatial ability could help students imagine physics phenomena, and students with low spatial awareness need the assistance of visual materials to learn physics concepts.…”
Section: Relevant Factors That Influence Reading Comprehension and Hands-on Manipulationmentioning
confidence: 99%
See 2 more Smart Citations